2013
DOI: 10.4067/s0718-221x2013005000026
|View full text |Cite
|
Sign up to set email alerts
|

Propiedades químicas, color y humectabilidad de partículas de Laureliopsis philippiana (tepa) con y sin tratamiento térmico

Abstract: El propósito de este trabajo fue determinar el efecto de un tratamiento térmico, en una atmósfera saturada de vapor de agua, en partículas de madera de la especie Laureliopsis philippiana. Las partículas fueron tratadas en autoclave a 150 ºC por 90 minutos y a una presión de 430 kPa, la cual se generó durante el proceso por la evaporación del agua en el autoclave herméticamente cerrado. Se determinaron la cantidad de extraíbles en soda, etanol tolueno, agua caliente y fría, así también, los porcentaje de celul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 10 publications
8
12
0
1
Order By: Relevance
“…This trend is in agreement with results reported by Tomek (1966), Boonstra et al (2006) and Poblete and Peredo (1990). The increase in the amount of extractable hydrophobic compounds and the reduction in wettability in treated L. philippiana particles determined by Crespo et al (2013), could explain the changes in the physical properties. Crespo et al (2013) also reported a signifi cant reduction in the pH value (6.7 to 4.8) and an increase in acidity, which favors the adhesive setting process (UF), contributing to the improvement in physical properties.…”
Section: Swelling and Water Absorption After 2 And 24 Hours 312 Busupporting
confidence: 82%
See 3 more Smart Citations
“…This trend is in agreement with results reported by Tomek (1966), Boonstra et al (2006) and Poblete and Peredo (1990). The increase in the amount of extractable hydrophobic compounds and the reduction in wettability in treated L. philippiana particles determined by Crespo et al (2013), could explain the changes in the physical properties. Crespo et al (2013) also reported a signifi cant reduction in the pH value (6.7 to 4.8) and an increase in acidity, which favors the adhesive setting process (UF), contributing to the improvement in physical properties.…”
Section: Swelling and Water Absorption After 2 And 24 Hours 312 Busupporting
confidence: 82%
“…Hsu et al (1988) reported that thickness swelling was reduced from 12.1 % to 3.6 % and linear expansion from 0.48 % to 0.24 %. In the case of boards manufactured with hygrothermally treated particles and UF, the improvement of the dimensional stability could be related to the increase in extractable hydrophobic compounds by hemicelluloses degradation, reported in hygrothermally treated L. philippiana particles by Crespo et al (2013). As reported, the increase in acidity in hygrothermally treated L. philippiana particles also contributed to an improvement in board dimensional stability, since this chemical change allows for better setting of the UF, improving the particle-adhesive-particle association.…”
Section: Swelling and Water Absorption After 2 And 24 Hours 312 Bumentioning
confidence: 68%
See 2 more Smart Citations
“…Similar al caso anterior, tres muestras de necromasa lignino-celulósica (tres repeticiones), de N. betuloides y S. conspicua, correspondientes a cada categoría de descomposición se secaron en una estufa a 70 o C durante 8 días, hasta peso constante. La determinación de celulosa se realizó mediante el método de Kurschner & Hoffer, usado por Crespo et al (2013). Dicho método consistió en depositar 1 g de aserrín de madera seca (molido a 40 -60 mesh), libre de extraíbles (TAPPI 204 cm-97) en un Erlenmeyer y mezclar con 20 mL de etanol y 5 mL de ácido nítrico concentrado.…”
Section: Categorías Característicasunclassified